Relevance of Serum Ferritin Levels with Severity of Dengue Fever and Thrombocytopenia; A Prospective Study - Rashid, Ahmar; Yaseen, Nidda; Siddiqi, Fuad Ahmed; Khan, Imran; Siddiqi, Kanaz Ahmed; Yaseen, Laila (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the relevance of increasing levels of serum ferritin with the severity of dengue fever and platelet count. Study Design: Prospective longitudinal study. Place and Duration of Study: Medicine Department, Combined Military Hospital, Rawalpindi Pakistan, from Jul to Nov 2023. Methodology: 110 admitted cases of dengue were selected. Serum ferritin levels and platelet count were done on day one and five of the indoor stay. The levels of serum ferritin were then compared with the severity of dengue. According to the WHO, patients without warning signs of dengue were classified as grade A, those with warning signs as grade B, and patients with severe dengue were classified as grade C. Results: The levels of Serum ferritin rose significantly on the day five. On day one, the median ferritin was 600.0 (812.5–350.0) ng/ml and median ferritin on day 5 was 1100.0 (2000.0–646.50) ng/ml. Our study results showed that serum ferritin level was increased at day 5 with a statistically significant p-value <0.001. Sixty-three (57.3%) had grade A, 31(28.2%) had grade B and 16(14.5%) had grade C dengue. Hyperferritinemia was observed in 47%, 27%, and 16% of grade A, B, and C patients, respectively. Correlation of Serum Ferritin with Platelet count at day one and day five showed that patients had thrombocytopenia with raised serum ferritin level at day five. Conclusion: The severity of dengue fever is correlated with elevated blood ferritin levels, which is quite relevant.